Studi Deskriptif Perilaku Penggunaan Internet di kalangan Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako - Abd. Syukur, Muh. Syarif S. (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2021)
This study aims to describe the behavior of internet use among students of the Faculty of Teacher Training and Education, Tadulako University. The type of research used is quantitative research with survey methods. There are 3 variables in this research, namely human resources, internet facilities, and supporting facilities. The results showed: 1) All FKIP Universitas Tadulako students were able to use the internet with a percentage of 100%. 2) All FKIP Universitas Tadulako students had devices to access the internet, 42% had laptops and 100% had smartphones. 3) All students of FKIP Universitas Tadulako were covered by internet network with the category of internet speed of 15.67% very fast, 43.63 % fast, 29.65 % quite fast, and 11.06 % slow.